Field notes contributed by Erik Munson, summer 1987 - Munson, Eriket al (1987)
Summer report of birds found in and around central Iowa contributed by Erik Munson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1987. Epson - sheet feed/flatbed